Effective Internal Audits Cut Fraud in Indonesia: Audit Internal yang Efektif Memangkas Kecurangan di Indonesia - Cindy Andriana Puspitasari; Dina Dwi Oktavia Rini (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effectiveness of internal audits in managing regional property fraud tendencies in Prigen District, Pasuruan Regency over five years. Utilizing qualitative methods, data was collected through interviews, observations, and documentation, and analyzed using Nvivo software. Despite the Pasuruan Regency Government consistently achieving